BASIS NILAI-NILAI PERDAMAIAN: SEBUAH ANTITESIS RADIKALISME AGAMA DI KALANGAN MAHASISWA - Nurudin Nurudin (Harmoni, 2013)
This paper is the result of a survey in private religious university in 10 provinces in Indonesia which potentially has religious radicalism among students. The conceptual model used in this study is the construction of radicalism measured by several indicators: things that are based on the theological, the models and strategies of political radicalism. The pattern of religious radicalism among students measured in four levels which are still settles. Firstly, radicalism latent in students` theological consciousness in the religious life. Secondly, have entered the realm of strategic awareness for the actualization of religious messages. Third , the tendency to act more conditional , rational and pragmatic. Fourth, radicalism that leads to religious behavioral that manifested in violence , terror , suicide bombings , and attacks on groups considered at odds with their religious understanding . The potential of therapy radicalism among students is the basis of the values of peace in socio - religious - conflict resolution due to the religious radicalism among students .